Right to know: case study of South Africa - Chacha, John Masaka (Department of Public Law, 2023)
The Republic of South Africa became democratic after it succeeded to come out of a long time 'scourge' of the apartheid system which violated quite a number of human rights. One of the tools employed during that era was unnecessary secrecy which hampered citizen's right to know. When South Africa held its first election in 1994 it commenced a new South Africa without apartheid; it aimed at embracing human rights and to do away with all bad laws existing before a democratic South Africa. Consequently, the supreme law of the Country, the Constitution of 1996, entrenched human rights law amongst which is the right to access to information held by the State and another person that is required for the 'exercise and protection of human right'. This was underscored in section 32. This right started to ·appear in the interim constitution of South Africa of 1993, but was amended in the current constitution by the addition of a subsection which directed that 'national legislation must be ena~ted to give effect to this right ... ' The provision of the Constitution was effected by enacting a legislation of the Promotion and Access to Information Act of 2000) (PAIA) which put in practice the directive of the Constitution. This minor dissertation intends to make a follow up of how this right is being implemented in South Africa. In doing so, the right to know will be examined in relation to institutional and cultural secrecy. Briefly, the dissertation will seek to answer the questions: i) what are the legislative norms which have been put in place to promote and safeguard this right? and ii) are there limitations and challenges to this right? Then at the end of this dissertation, the research will present a comparative study with Tanzania, the country of origin of the present author, where the right to know is recognized by the Constitution of Tanzania but remains ineffective for lack of concrete laws to enforce the right of access to information. In a state where there is no law providing for public access to government information, this work can present a lesson from South Africa. Furthermore, it is hoped that this dissertation can contribute ideas at this moment when Tanzania is in a · transitional process of making a new Constitution.